LIBRARY SERVICES FOR OPEN AND DISTANCE EDUCATION (NAU Journal of Library and Information Science, 2021)
Every learner should have access to well- organized library services throughout the period of his/her studies. Open and distance education provides education for all and promotes lifelong learning. The members of the distance learning community are entitled to library services and resources equivalent to those provided for students in traditional campus setting. The paper focused on library services available to distance learners. Keywords: Library Services, Open Distance Education, Information Resources, Information Communication Technology. IntroductionMan’s quest for growth and development is founded upon the available information for operations and management of everyday activities. Information according to Ezekwe and Muokebe (2012) is a valuable national resource that is useful at personal, community and national levels and for economic, cultural, technological and social developmental purposes. As a resource, information is valuable, powerful and marketable. In response to the great importance of information, libraries are founded to play critical roles. Ogbonna (2009) observe that libraries these days function as agents of educational, economic, socio-cultural and political changes such that they reflect their definitions. This author further defines the library as a place where books and other forms of human records are professionally acquired, organized and made available for use. While Ezekwe and Muokebe (2012), define the library as an organized, carefully selected collection of books and non-book materials managed by librarian(s) who interpret(s) the content of these materials in the process of use. The library is made up four main components: the building, the staff (personnel), the information resources and the user.The major reason for setting up libraries according to Ogbonna (2009) is to stimulate education advancement. Bhatti and Jumani (2012) posit that the library is an indispensable instrument of education; the library is the central nervous system of any educational process. Libraries are indispensable to the teachers as well as the students. This may explain why the Federal Government of Nigeria in the National Policy on Education (2010) states, that libraries are one of the most important educational services. Every state ministry needs to provide funds for the establishment of libraries in all our educational institutions and to train librarians and library assistants for this service. Education as a whole depends on the resources available in the library and it is essential that every learner should have access to well- organized library services throughout the period of his or her studies. Lifelong education is ensured through the provision of diverse resources and on continued basis, whether the learner is in a conventional system or in open and distance education programmes.Face- to-face interaction between students and teachers in the classrooms of educational institutions is traditional and widespread. This conventional system of education according to Gopakumar and Baradol (2009) cannot accommodate all aspirants, whose numbers are ever increasing. This has resulted in devising alternative methods of education to satisfy demand. Distance students’ characteristics are different from students in traditional institutions. According to Ngimwa (2008) the distance students are generally adult learners, mature, employed and have family responsibilities. They have higher motivation and are willing to take responsibility for their education. Distance students are self-directed, study on independent basis, learn in a variety of ways and take control over their learning.Open and Distance Education in NigeriaDistance education is a means of providing access to basic and tertiary education for most Nigerians that may not had the opportunity and wherewithal for regular formal education (Eze and Uzigwe 2012). Federal Government policy statements have emphasized the determination of the government to make a success of the programme (National Policy of Education NPE, 2010). The policy gave the following as the objectives of distance education:· Provide access to quality education and equity in educational opportunities for those who otherwise would have been denied.· Meet special needs of employers by mounting special certificate courses for their employees at their work place.· Encourage internationalization especially of tertiary education curricular.· Ameliorate the effects of internal and external brain drain in tertiary institutions by utilizing Nigerian experts as teachers regardless of their locations or places of work.The objectives of distance education according Akanimidu (2016) cannot be achieved easily without the supporting aids of education such as libraries, materials for instruction-based media formats, audio-visual equipment, funding and human resources.Virtually all the tertiary institutions in Nigeria; Colleges of Education, Polytechnics and Universities are providing distance or part-time education. However, there are two national institutions established to provide distance learning. National Open University of Nigeria (NOUN) for university education and National Teacher’s Institute (NTI) for higher teacher education. NTI was established by Federal Government of Nigeria in 1976. The Institute was charged with the responsibility of providing courses of instruction leading to the development, upgrading and certification of teachers as specified in the relevant syllabuses using distance education techniques.The federal government of Nigeria has been concerned on how to cater for the teeming vibrant populace who are not absorbed by any of the existing higher institutions. To ameliorate this situation, Igwe (2010) states that NOUN was formally established in 1983. It was closed in 1984. In 2002, the defunct Open University of Nigeria was resuscitated and reactivated as NOUN. According to Igwe (2010) there are about 30000 registered students from all classes of the society. There are about 33 study centres across Nigeria. Course materials are centrally produced at the headquarters and dispatched to the study centres. Students register, collect course materials and attend tutorial facilitation at the study centres.Open and distance education provides education for all and promotes lifelong learning in Nigeria. It fills the gap created by the closure of sub-standard outreach/satellite campuses across the nation. The mode of education delivery system is flexible which will help meet up with the economic realities where a lot of people desire to work and learn simultaneously.Open and distance education helps in the provision of education to girls and women who cannot leave their homes regularly (as they live in purdah). It responds effectively to the growing demand of working adults or any others who have difficulties in getting training in conventional education because of lack of flexibility in the timing and duration of academic programmes.The structure of library and information services in NOUN is hybrid (Igwe 2010). Three centres are being developed with library services: headquarters in Lagos, Abuja office and Kaduna campus. The hybrid library at NOUN headquarters has collections in various formats. It has the electronic resources section with high speed internet facilities and a range of electronic resources and databases.Library Services for Open and Distance Learners The provision of quality library services to those who learn at a distance is one of the challenging developments that have occurred in contemporary librarianship. Watson (2013) observes that distance education has led to the development of specialized library and information services that can be called “Distance Education Librarianship”. Watson defined a distance librarian as a specialized academic librarian whose primary duties involve serving the information needs of distance education students, faculty and staff. This position involves coordinating the duties of many librarians and library staff to ensure adequate access to library resources for those who enroll in and teach distance education courses.The guidelines for distance learning library services developed by the Association of College and Research Librarians (ACRL) (2004) reiterate that members of the distance learning community are entitled to library services and resources equivalent to those provided for students in traditional campus setting. Gandhi (2013) states that library support to distance learners is also vital because of the curriculum requirements student and faculty research needs and the importance of information literacy. The library needs of distance learners are the same as that of on-campus students. The basic library and information services distance learners need according to Adesoye and Amusa (2012) are;· Access to information resources such as texts, supplementary reading and reference services· Learning how to find the information they need from the information that is available· Developing ways to apply the information learned to make sound information-based decisions.Traditionally, librarians have been responsible for providing reference services to students and staff on campus; guiding patrons to appropriate materials; building library collections to support curriculum objectives of programmes; being custodians of archival materials; enhancing access to materials through inter-library loan and increasing information literacy by training students in the effective use of libraries through bibliographic instruction. Since distance learners cannot come to the library, library resources and services must be delivered to them electronically or through other means.In distance education the librarian’s role as stated by Adesoye and Amusa (2012) are:1. To ensure that library and information services conform to accreditation requirements.2. Develop and maintain quality distance education information resources such as reading lists for students and course developers (educators, team leaders, media production personnel).3. Help distance learners acquire library skills, critical thinking, study and information literacy skills.4. Advise distance educators on new and appropriate course materials.5. Support the research and scholarship activities of distance education faculty.6. Identify other institutions that can assist in delivering distance library services to students.To fulfill these roles and responsibility, librarians are expected to possess a wide-ranging arsenal of skills. Traditional skills such as reference, collection development and library instruction must be supplemented with in-depth knowledge of the internet and www; marketing and legal issues related to copyright, fair use and electronic licensing time management, ability to negotiate, work collaboratively and communicate with a diverse clientele.Distance learners access library and educational resources and services in various ways according to Bhatti and Jumani (2012). Access can be direct e.g face-to-face, or mediated by printed material, e.g manuals, brochures, or mediated by technology, using a variety of media such as telephone, voicemail, website, email. Library services are essential support services to distance education students. Bhatti and Jumani also note that the library needs of distant learners are not unique; they have the same library and information needs as on-campus students. Apart from the manner in which they are accessed, requested and delivered, the same resources are required, the same questions are asked and the same quality of service is expected; and they expect the same level of library service as that provided to their peers on campus.The advent of Information Communication Technology (ICT) according to Igwe (2010) has dramatically transformed every segment of society particularly information collection, processing, storage, retrieval and dissemination. Technology has given us the opportunity and privilege of creating libraries without walls. Library Without Walls (LWW) according to Jagannathan (2006) is a phrase that describes a library without physical infrastructure such as library building, operational sections, reading and stack rooms, circulation counter, furniture, equipment, collections in diverse media and so on. They are embedded into a virtual library and accessed through internet from any computer system; desktop or laptop. Igwe (2010) observes that, books are no longer like bricks in the walls of libraries rather they are converted into bits and bytes to create LWW.Technology has enabled distant learners to have access to a wide range of library services and unlimited opportunities for librarians to assist these students. Igwe (2010) is of the view that books once hoarded in stacks can be scanned into computers and made available to anyone, anywhere almost instantly, over high-speed networks. Instead of fortresses of knowledge; there will be ocean of information. This transforms libraries from guardian of tradition to catalysts of a vast change. This will dissolve the barriers that separate libraries from their users.The following are some of the library services for open and distant learners as enumerated by Eze and Uzigwe (2012):1. Reference and referral services2. Access to library collections and information resources.3. Bibliographic instruction and information literacy skills.4. Inter-library loan/co-operation5. Document delivery.6. Reciprocal borrowing and resource-sharing agreement.Reference services traditionally provided to students include professional assistance with information research strategies, resource selection and mediated database searching. According to Thompson (2012) even though the fundamental concepts of good reference services remain constant in both on- campus and off-campus environments, providing reference and referral services to distance learners presents three opportunities and challenges for librarians. The opportunities and challenges are; Globalization of information, Increase in students’ expectations and the reference interview.In distance education environment, students can use forms to make research queries, either in print or electronically. In the form, “trigger” or prompt questions replace face-to – face assistance in helping the student to properly complete a request. Institutions that already have dedicated library telephone services can use them for distance librarian reference inquiries. Some institutions with web-based services purchase online versions of major reference works to provide distant learners with a convenient access point.Users’ expectations have skyrocketed. Students expect information wherever and whenever. Distance learners are generally non- traditional students trying to balance work, family and educational demands. According to Gandhi (2013), a significant number of these students carry out their library search in evenings and weekends, when the reference desk of the library is closed. They expect reference assistance and other library services to be available twenty-four hours a day, seven days a week (24/7). Academic libraries are adopting several strategies to cater for 24/7 service expectations of distance students. Many libraries have created web-based forms to enable students to send in reference service queries twenty-fours a day. Igwe (2010) states that libraries are forming regional, state-wide, national and even international partnerships and consortia to provide “live” virtual reference services to remote users for extended hours.Access to Information Resources and Library CollectionsGandhi (2013), states that the single most important contribution that librarians can make in support off-campus programmes is to ensure access to the resources required by the curriculum. Gandhi emphasized that having access to adequate library resources is the key to the success of distance learners. Academic librarians have been responsible for selecting, acquiring, providing access to, and managing library materials to meet curriculum needs of students and faculty.The shift from print to electronic collections has altered the role of librarians involved in selecting, acquiring and managing library collections. The process for selecting electronic resources is far different from that of selecting books and serials in the print. Librarians have to be more proactive in selecting electronic resources since faculty and students are seldom aware of electronic resources available in the market place and rarely recommend them for addition to library collections (Igwe, 2010). Library collections have primarily consisted of printed books and monographs. The traditional library collections are readily accessible to on-campus students, but are not accessible to distance learners who cannot come to the library. Restauri (2014), states that since the 1980s, many academic libraries have provided bibliographic access to the titles of materials in their collections via the Online Public Access Catalogue (OPAC). Gandhi (2013) observes that three important developments are helping academic libraries to improve access to books and monographs in the electronic format by distance learner: availability of reference books in aggregated or stand-alone electronic databases; Electronic books or E-books and Full-text books on the internet.Web-based Library and Information ServicesElectronic documents can be made available anywhere and anytime that two computers can connect. What make this possible is the World Wide Web, according to Gopakumar and Baradol (2009). With the technology of the web, library documents can be viewed and printed by any person who has web connected computer. The web opens new windows of opportunity to provide information support to distance learners.Some of the library and information services that can be offered over the web include:1. Library website as a service point.2. OPAC3. Electronic reference.4. Access to E-journals.5. E- Reserve.6. Information literacy.7. Online Reference sourcesLibrary Website as a Service PointA website, according to Gopakumar and Baradol (2009), is a hypermedia document or a collection of hypermedia documents that are linked together under a single subject or institution name. A university website can contain websites of its library and its faculty with a home page that is the starting point and which provides the users with key information required to locate resources within the site. Various services can be offered to distance students through the website of the library.Online Public Access Catalogue (OPAC) The Online Public Access Catalogue (OPAC) is the electronic version of a library’s catalogue. A web-based OPAC allows distance learners to browse the catalogue using search options such as author, title and subject. This according to Eze and Uzigwe (2012) helps the students to determine the availability of an item in the library. The library can also provide links to OPACs of other libraries, including those with consortia relationship.Electronic ReferenceEmail can be effectively used for providing reference service. A distance learner, according to Gopakumar and Baradol (2009), may be allowed to approach the library for reference needs through email. The student’s information request can be directed to a subject specialist and documents can be forwarded to the student. The process must be carried out cautiously, since the relevance of the document depends on how clear the student’s request is, and email does not allow a reference interview. Reference questions and the answers can be collected and made into a database. They can be indexed and later from this reservoir of reference questions a web page containing “Frequently Asked Questions” (FAQ) can be created and maintained.Access to E-journalsAny journal that is available over the Internet can be called e-journal. Some electronic journals are freely available. Others have charging mechanisms of different types. Gopakumar and Baradol (2009) observe that there are aggregators e-journals and they provide access to the full text content for authorized users. Usually they are IP-authenticated. This means that they are made available to computers with the specified IP numbers for which subscription is made. The publisher may issue some directly. Distance learners can be provided access to E- journals. They should be provided with user name and password to ensure that only authorized people use the information.E-ReserveLee 2012 describes E-reserves as collections of digitized information sources like periodical articles, notes, solved problems made available to the internet and which contain useful information for a specific course and recommended by the instructor. Students can download and print the material.Information LiteracyInformation literacy according to Gopakumar and Baradol (2009) is a person’s ability to identify, retrieve and use information through systematic methods. Information literacy sessions should be presented to distant learners using various means. Interactive sessions in digital format designed using animation techniques are provided on the website.Online Reference SourcesMajor reference sources are now available online. Encyclopedia Britannica (www.eb.com) and Oxford dictionary ( www.oxforddictionary.com) are good examples. The library website should also act as a knowledge portal. Links to various websites giving information on specific areas can be accumulated and provided on the website. This will help the students at single point for browsing (Gopakumar and Baradol 2009).The wealth of technology options available today enables the provision of library and information services to distance students in a way that can increase the quality of the courses. But there are certain factors that hinder the effective use of ICT in the open and distance education. Some of them as observed by Eze and Uzigwe (2012) include: paucity of ICT infrastructure and lack of access, absence of reliable computer network, high enrolments, inadequate funding to acquire adequate and good quality ICTs. Most distance learners do not have adequate access to electronic resources such as email, web pages, virtual libraries, online databases and inadequate ICT literacy.ConclusionLibraries are indispensable in every facet of education. Effective library support to learners is important for qualitative delivery of instruction and learning. Libraries have always been a major focus for all kinds of learning, formal or informal. The distant learners have the same library and information needs as conventional students.The challenge of providing library services to open and distance learners are enormous. However, technology has provided the impetus to break boundaries and reach the distance learners. ICT has become the main medium through which the distance education programmes are being facilitated.ReferencesAdesoya, A.E. & Amusa, O.I. (2012). Investigating the information needs of sandwich and part-time students of two public universities in Ogun state, Nigeria. http://unllib.unl.edu/IPP/ Library Philosophy and Practice 2012.Akanmidu, J. O. (2016). Distance learning in the digital age: The role of the National Library of Nigeria in Nigerbiblio 17 (1&2) 49-57.Association of College & Research Libraries Guidance (ACRL) (2004). Guidelines for distance learning library services: College & Researchlibraries News, 65(10), 604-611. Retrieved from http://www.ala:org/asla/acrl/acrlstards/standarolsguideline .Bhatti, A. J. & Jumani, N.B (2012). Use of libraries in open and distanceOnline Journal of distance education 13(3)1-18.Eze, J.U. & Uzigwe, G. U. (2012). Enhancing distance education through ICT: emerging roles of the library in Nigeria libraries 45(1)104-114.Ezekwe, F. A. &Muokebe, B. O. (2012). Introductory Studies in the use of the library and Information Technology. Enugu: RhyceKerex publishers.Federal Republic of Nigeria (2010). National Policy on Education. Revised edition, Lagos: Federal Ministry of Information.Gandhi, S. (2013). Academic librarians and distance education; challenges and opportunities in reference and user services Quarterly 43(2) 138-154.Gopakumar, V. & Baradol, A. (2009). Assuring quality in distance education for library and information Science: the role of library. In Library Philosophy and Practice. Retrieved from http:// unIIib.uni.edu/Ipp/gopakumarbaradol.htm.Igwe, U. O. (2010). Libraries without walls and open and distance learning in Africa: The Nigerian experience. Retrieved from wikieducator.org/images/9/95/PID399.pdfJagannathan, N. (2006). Library without walls for distance learners of South Asian Region; “A Dream Far-Fetched” The fourth Pan Commonwealth forum on open learning Jamaica. Retrieved from http://pcf.dec.uwi.edu/viewpaper.phil .Lee, S. D. (2012). Building an electronic resource collection: A practical guide. London: Library Association.Ngimwa, P. (2008) An African experience in providing a digital library service: the African virtual university example. The fourth pan commonwealth forum on open learning. Retrieved from http://pcf.dec.uwi.edu/viewpaper.phd.Ogbonna, I. M. (2009). Appreciating the library. Enugu: His Glory publishers.Restauri, S. L. (2014). Creating an effective online distance education programme using targeted support factors. TechTrends, 47, 21-41.Thompson, H. A. (2012). The library’s role in distance education; survey results from ACRL’s 2000 academic library trends and statistics. College and Research Libraries News 63;339 349.
Keywords: Library Services; Open Distance Education; Information Resources; Information Communication Technology